Influence of the volume of soft tissue herniation on clinical symptoms of patients with orbital floor fractures. Issue 12 (December 2016) - Safi, Ali-Farid; Richter, Marie-Theres; Rothamel, Daniel; Nickenig, Hans-Joachim; Scheer, Martin; Zöller, Joachim; Kreppel, Matthias
Abstract: Introduction: One of the most important complications of orbital floor fractures is diplopia and restricted ocular movement. The role of the volume of soft tissue herniation on these clinical symptoms after orbital floor fractures is unclear and potentially may predict development of persistent clinical symptoms. Therefore the aim of this study was to assess pre- and postoperative complications associated to the volume of soft tissue herniation, with special interest to diplopia and bulbus motility impairment. Material and methods: 204 untreated patients with orbital floor fractures from 2009 to 2011 were included in this retrospective study. Contingency tables and χ 2 -test were performed to analyze associations between two qualitative variables. p-Values p < 0.05 were considered as significant. Volume measurement was performed in a semiautomatic segmentation method with the software "ITK-Snap". Results: The volume of soft tissue herniation correlated significantly with pre- and postoperative diplopia (p = 0.003; p = 0.002), persistent diplopia (p = 0.009) as well as pre- and postoperative bulbus motility impairment (both p < 0.001). Furthermore we found out significant associations between the volume of soft tissue herniation and pre- and postoperative complications depending on fracture type and reconstruction technique. Conclusions: Volume measurement of soft tissue herniation may help to predict postoperative complications, particularly bulbus motility restriction and persistent diplopia. The risk for these symptoms rises with increasing volume of soft tissue herniation after orbital floor fractures. Therefore we recommend for these patients within indication an early repair and/or closer observation.